Treatment failure patterns are similar between p16− and p16+ oropharyngeal squamous cell carcinomas. Issue 4 (1st June 2022) - Hamill, Chelsea S.; Muller, Richard Grant; Clancy, Kate; Vu, Brandon; Gui, Shanying; Thuener, Jason Eric; Wasman, Jay; Li, Shawn; Fowler, Nicole; Rezaee, Rod; Lavertu, Pierre; Teknos, Theodoros N.; et al.
Abstract: Background: The incidence of p16+ oropharyngeal squamous cell carcinoma (OPSCC) has been increasing. The notion that p16+ OPSCC has a propensity for atypical and disseminating metastasis has gained traction. We compared treatment failure patterns in p16+ and p16− OPSCC and evaluated survival impact. Methods: Retrospective analysis of patients with recurrent/metastatic OPSCC disease between 1/2009 and 12/2019. Results: Thirty‐eight p16+ and 36 p16− patients were identified. Three distinct failure patterns (distant vs. locoregional, atypical vs. typical, and disseminating vs. non‐disseminating) were studied. No significant differences were found between p16+ and p16− patients. Multivariate analysis showed p16 status was an independent prognostic biomarker; p16+ patients have a favorable overall survival compared to p16− patients (HR 0.34, 95% CI 0.16–0.77; P  = .005). Conclusions: We challenge the view that p16+ OPSCC exhibits a distinctive treatment failure pattern and showed that p16 status impacts patient survival independent of disease progression. Abstract : The incidence of p16+ oropharyngeal squamous cell carcinoma (OPSCC) has been increasing. The notion that p16+ OPSCC has a propensity for atypical and disseminating metastasis has gained traction. No significant differences were found between p16+ and p16− patients and three distinct failure patterns (distant vs. locoregional, atypical vs. typical, and disseminating vs. non‐disseminating). We challenge the view that p16+ OPSCC exhibits a distinctive treatment failure pattern and showed that p16 status impacts patient survival independent of disease progression.